The mechanical properties of Polyvinyl Butyral (PVB) at high strain rates - Zhang, Xihong; Hao, Hong; Shi, Y.; Cui, J. (Elsevier Ltd, 2015)
Polyvinyl Butyral (PVB) has been largely used as an interlayer material for laminated glass to mitigate the hazard from shattered glass fragments, due to its excellent ductility and adhesive property with glass pane. With increasing threats from terrorist bombing and debris impact, the application of PVB laminated safety glass has been extended from quasi-static loading to impact and blast loading regimes, which has led to the requirement for a better understanding of PVB material properties at high strain rates. In this study, the mechanical properties of PVB are investigated experimentally over a wide range of strain rates. Firstly, quasi-static tensile tests is performed using conventional hydraulic machine at strain rates of 0.008–0.317 s−1. Then high-speed tensile test is carried out using a high-speed servo-hydraulic testing machine at strain rates from 8.7 s−1 to 1360 s−1. It is found that under quasi-static tensile loading, PVB behaves as a hyperelastic material and material property is influenced by loading rate. Under dynamic loading the response of PVB is characterized by a time-dependent nonlinear elastic behavior. The ductility of PVB reduces as strain rate increases. The testing results are consistent with available testing data on PVB material at various strain rates. Analysis is made on the testing data to form strain-rate dependent stress–strain curves of PVB under tension.